Model tekstualnega nadzora - Packard, Stephan (Primerjalna književnost, 2008)
A basic theory of textual control is presented, outlining a communicative model that traces the contest at the heart of any case of censorship as a contradiction in representation. Some special relations between literature and textual control are discussed.
Keywords: literatura in cenzura; komunikacija; komunikacijski modeli; tekstna analiza